Organizational slack effects on innovation: the moderating roles of CEO tenure and compensation - Mousa, Fariss-Terry; Chowdhury, Jaideep (Journal of Business Economics and Management, 2014)
This study draws on upper echelons theory, the resource based view, and Penrose’s theory of firm growth to show that slack resources, specifically financial and human slack, are essential to the research and development (R&D) strategies of organizations. We also suggest that both Chief Executive Officer (CEO) tenure and CEO compensation positively moderate the slack-innovation relationship. The empirical design compromised of panel regression analysis. We tested our hypotheses using all US publicly traded firms between 1993 and 2011. The research results show that firms with excess financial resources are more likely to have higher R&D investments, and to completely understand this relationship we must study CEO tenure and compensation. This study sheds light on central antecedents of firm innovation, it further extends our understanding by investigating the impact of CEO tenure and compensation on the slackinnovation relationship, and it applies a longitudinal design which answers previous calls to investigate this topic in more depth by offering enhanced stability to the results while allowing for different economic scenarios.